(De)legitimating extractivism: the shifting politics of social licence. Issue 4 (7th June 2019) - Gunster, Shane; Neubauer, Robert J
ABSTRACT: Most scholarly accounts of social licence define it as a public relations strategy to legitimate resource development. In Canadian pipeline politics, however, it has had the opposite effect, crystallizing widespread concerns about industry capture of regulatory processes and affirming the democratic rights of local communities. This assessment of the concept's critical, counter-hegemonic potential to challenge the policies, practices and logic of state-sponsored extractivist development situates social licence as a key discursive battleground in the struggle between politicization (which accents agonistic confrontation between competing alternative futures) and de-politicization (which defuses conflict and builds consensus around the perception of common interests). Frame analysis of news media and advocacy group texts is used to investigate how opponents of a pipeline project bridged the idea of social licence with movement frames concerning identity, injustice and democratic agency to transform the concept from a public relations term meant to enable corporate activity into a critical trope used to constrain it.